Peningkatan Ketrampilan Berbicara Anak Usia Dini Melalui Kegiatan Bermain Peran (Penelitian Tindakan Kelas Pada Kelompok B Paud Anak Sholeh Purwokerto) - Ilva Dwi Mulyana (SALIHA: Jurnal Pendidikan & Agama Islam, 2018)
This study aims to improve speaking skills in early childhood early childhood Children Sholeh Purwokerto. This research is a class act who adapted from Suharsimi Arikunto. The study consisted of two cycles and each cycle consisted of three meetings. Data collection techniques gained through observation, documentation, interviews. Subjects in this study were children in group B ECD Children Sholeh Purwkerto the 16 children with details of nine boys and seven girls. Data analysis was performed by descriptive analytic. The success of the student is determined criteria ≥75%, it means the student is successful if achieving ≥ 75% of goals or values that should be achieved, less than the otherwise poorly managed. The results showed that the learning outcomes of students' speaking skills through activities that play an increasing role. Before speaking skill attainment measures the percentage of only 61.01%. In the first cycle speaking skills increased to 63.19%, thus the percentage increase between prior action and the first cycle was 2.18%. In the second cycle increased speaking skills become 88.48%. An increasing percentage of speakingskills early in the first cycle and the second cycle is equal to 25.29%.